THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP ON NURSE PERFORMANCE IN TUBERCULOSIS TREATMENT: A NARRATIVE REVIEW - Ayu Afriani Panyuwa; Luky Dwiantoro (Nurse and Health: Jurnal Keperawatan, 2021)
Background: World Health Organization (WHO) has established a Directly Observed Treatment Short-Course (DOTS) strategy. Carrying out the DOTS strategy, the public health center is running the TB Prevention and Treatment program, in Indonesia it is called prevention and countermeasures of tuberculosis (P2TB) but in reality, the P2TB program has not been effectively implemented. Health workers who play an important role in carrying out their roles and duties in society are nurses. One of the efforts to improve the performance of nurses in TB treatment is the application of transformational leadership. The purpose of this literature review is to examine the results of the past 10 years of research related to the influence of transformational leadership on nurse performance in tuberculosis treatment. Design: This study design is a literature review to search and review article from database and theory underlying this study or guidance in this literature review using Preferred Reporting Items for Systematic Reviews and PRISMA. Data Sources: The data base used in the article searches used include: Science Direct, PubMed, Google scholar, EBSCO using the keywords transformational leadership, nurse performance, tuberculosis treatment. The articles used are those between the years 2009-2019. Review Methods: The review method for this literature review using a narrative method by classifying the similar extracted data according to the research findings. Results: The main component of transformational leadership to improve The performance of nurses to play a more optimal role in an effective and efficient TB treatment effort is an idealized influence, which is that nurses have charismatic, in the fact that nurses in providing nursing care in the community must provide good paragons and become role models in the field of good health to individuals, families, groups and communities about how to live clean and healthy as behavior that can be imitated by the community, inspirational motivation for nurses as health teacher educators or health counselling which is a part of health promotion, the nurse's intellectual stimulation empowers communities to solve health problems in the community through small group discussions, and individual consideration, in this case the nurse's duty is as an advice provider and counseling is highly important and beneficial for the community. In order to achieve the fulfillment of the roles and responsibilities of nurses, there must be inner motivation among nurses in order that they can provide decent motivation to the community. Conclusion: Transformational leadership can be applied to improve the performance of nurses in TB treatment efforts.